TRAINING PRACTICE AS AN INTEGRAL COMPONENT OF PROFESSIONAL DEVELOPMENT FOR FUTURE LAND MANAGEMENT ENGINEERS - Nesterenko , Г. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The organization of training practice is crucial for the professional development of specialists in geodesy and land management. Effective training necessitates a comprehensive understanding of its importance, as well as the careful selection of appropriate forms, content, and methods at each stage of the educational process. Only by integrating training into the overall framework of professional education, while considering its key structural components, we can ensure the development of essential professional competencies. The relevance of high-quality training for future specialists in geodesy and land management underpins the choice of this topic. This article aims to elucidate the unique aspects of organizing training practice for future specialists in geodesy and land management, with a focus on a practice-oriented approach. Practical training for students is a mandatory and vital component of the educational and professional program for specialists in geodesy and land management. This training enhances and reinforces the professional knowledge, skills, and competencies acquired in the university classroom. The primary objective of practical training is to empower students to master both theoretical and practical knowledge, familiarize themselves with the latest technologies, and develop professional competencies for independent decision-making. Additionally, it helps them continuously update their knowledge and adapt psychologically to real-world workplace conditions. The qualification of a young specialist is evaluated based on their ability to apply their acquired knowledge and skills to tackle production-related problems that involve planning and managing production processes. Practical training occurs during practical and laboratory classes in professional disciplines as well as through internships at geodesy and land management companies. The article describes the main stages of practical training, namely the introductory, educational and technological, and the production and professional stage. The criteria for readiness for professional activity encompass several key aspects, including professional awareness, adaptability in various production scenarios, practical action expediency, development of organizational abilities, communication skills, etc.